COMPUTER APPLICATION TRAINING FOR UPT BPPRD SUKARAME STAFF AND OFFICIALS - hilda yunita; Devi Rista; Firdia Riani (Universitas Nahdlatul Ulama Lampung, 2020)
Formerly, UPT BPPRD Sukarame Area always has difficulty in financial statement to local government making. This trouble was caused by condition which no human resource who able mastery and used computer program of financial statement and financial statement way to local government. Because of that situation, every staff and official mastery computer program especially related to financial statement. Actually, financial statement has been created by staff, but it still used manual way neither computer program. Team expected that with this computer utilization training, staff and officials could used standard financial statement program like microsoft excel and power point. The target of this community dedication was staff and officials of UPT BPPRD who able to make computer based financial statement and they able to apply Microsoft Powerpoint for presenting financial statement. This training program did as schedule plan. Based on feedback, response, and participation of UPT staff and officials concluded that they feel satisfied with this training program. It proved by ability to apply computer program as requisite in office.